Health-related quality of life and risk of hospitalization in a healthy general population. (13th November 2019) - Bonaccio, M; Di Castelnuovo, A; Costanzo, S; Persichillo, M; De Curtis, A; Cerletti, C; Donati, M B; de Gaetano, G; Iacoviello, L
Abstract: Background: The association of health-related quality of life (HRQL) with total and cardiovascular (CVD) hospitalization was assessed in a population-based cohort of apparently healthy subjects; several pathways possibly accounting for such associations were also tested. Methods: Longitudinal analysis on 16, 849 subjects free from CVD and cancer from the Moli-sani Study, Italy (2005-2010). HRQL was performed by the 36-Item Short Form Health Survey including both mental and physical domains. First hospital admissions were recorded by direct linkage with hospital discharge form registry. Hazard ratios (HR) with 95% confidence interval (95%CI) were calculated by multivariable Cox-regression. Results: Over a median follow-up of 7.3 y, 6, 061 all-cause, 1907 CVD, 431 IHD and 294 stroke hospital admissions were ascertained. The highest quintile of mental HRQL was associated with 23% (95%CI: 17% to 29%), 26% (15% to 36%) and 30% (5% to 48%) lower risk of total, CVD and IHD admissions to hospital, respectively, as compared to the lowest. Risk estimates for physical health were 0.60 (0.56-0.65 for Q5 vs Q1), 0.57 (0.50-0.65) and 0.73 (0.55-0.97) for total, CVD and IHD hospital admissions, respectively. A downward trend with stroke hospitalizations was found for both mental and physical HRQL. Healthy behaviours explained up to 13% of the association between mental HRQL and IHD risk; inflammatory markers (i.e. C-reactive protein and white blood cell count)) accounted for a significant proportion (34%) of the association of physical HRQL with IHD hospitalizations. Conclusions: In a large sample of disease-free subjects, not only physical, but also higher mental HRQL is associated with lower risk of total and CVD hospitalizations. Key messages: HRQL adds meaningful information beyond traditional risk factors to the prediction of hospitalization. HRQL assessment may be useful in stratifying hospitalization risk among a general population of healthy adults.